2019
DOI: 10.1021/acs.jpcb.9b07075
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Modulation Stimulated Raman Scattering Microscopy through Polarization Encoding

Abstract: Stimulated Raman scattering (SRS) microscopy is a powerful method for imaging molecular distributions based on their intrinsic vibrational contrast. However, despite a growing list of biological applications, SRS is frequently hindered by a parasitic background signal which both overpowers the signal in low-signal applications and makes the extraction of quantitative information from images challenging. Frequency modulation (FM) has been used to suppress this parasitic background. However, many FM-SRS methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…40 An approach that would allow DNA imaging even in interphase was later demonstrated by using a distinct spectral feature of DNA in the C-H stretching region which when coupled with linear decomposition allowed a higher sensitivity DNA imaging than that found in the fingerprint region which could help add better nuclear morphology and architecture than current SRH techniques. 15 Hill et al, 41 were able to further enhance imaging of DNA within this region by using a polarisation encoded FM-SRS technique designed to isolate spectral contributions from low-signal species. By tuning the frequency difference so that there is a roughly equivalent contribution of protein at each vibrational transition measured during the frequency modulation it can be cancelled out, highlighting any contribution from DNA C-H stretches in the 'on-resonance' portion.…”
Section: Second Harmonic Generation and Other Non-linear Modalitiesmentioning
confidence: 99%
“…40 An approach that would allow DNA imaging even in interphase was later demonstrated by using a distinct spectral feature of DNA in the C-H stretching region which when coupled with linear decomposition allowed a higher sensitivity DNA imaging than that found in the fingerprint region which could help add better nuclear morphology and architecture than current SRH techniques. 15 Hill et al, 41 were able to further enhance imaging of DNA within this region by using a polarisation encoded FM-SRS technique designed to isolate spectral contributions from low-signal species. By tuning the frequency difference so that there is a roughly equivalent contribution of protein at each vibrational transition measured during the frequency modulation it can be cancelled out, highlighting any contribution from DNA C-H stretches in the 'on-resonance' portion.…”
Section: Second Harmonic Generation and Other Non-linear Modalitiesmentioning
confidence: 99%
“…However, directly increasing the laser powers can easily cause irreversible effects on the sample or affect the biological dynamics in living cells and the sample concentration (eg, intracellular protein, lipid, DNA, … content) is often fixed. Additionally, general methods to reduce noises are to develop special system designs [20, 23, 28], which increases the cost, complexity and incompatibility of the SRS system.…”
Section: Theory and Experiments Setupmentioning
confidence: 99%
“…Nevertheless, the power of the excitation lights and the pixel dwell time have to be kept under a safe level to avoid photodamage to the biological specimens and affecting the biological dynamics in living cells/body. The high‐frequency modulation and the frequency‐modulation denoising [23] can only achieve limited improvement and requires a device update or special design of the system. The widely used balanced detection will probably help but the noncollinear balanced detection is complicated to achieve an ideal equivalence of intensities and phase of the two detected (signal and reference) beams because the optical transmission of the sample varies during scanning and it only works against laser noise [24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that, among these crystals, the SrMoO 4 and SrWO 4 crystals are the most perspectives for SRS generation on both stretching and bending modes of internal anionic group vibrations with the strongest SRS pulse shortening under synchronous laser pumping. The significant progress in applying the methods of SRS and CARS (Coherent Anti-Stokes Raman Spectroscopy) in recent years was achieved in biology and medicine [11]- [17]. For example, in [11] it was reported a new procedure for alignment-free frequency modulation SRS utilizing polarization encoding since the SRS microscopy is a powerful method for imaging molecular distributions based on their intrinsic vibrational contrast.…”
Section: Introductionmentioning
confidence: 99%
“…The significant progress in applying the methods of SRS and CARS (Coherent Anti-Stokes Raman Spectroscopy) in recent years was achieved in biology and medicine [11]- [17]. For example, in [11] it was reported a new procedure for alignment-free frequency modulation SRS utilizing polarization encoding since the SRS microscopy is a powerful method for imaging molecular distributions based on their intrinsic vibrational contrast. The successful application of polarization-sensitive SRS imaging in treating skin, nail, and fungal infections was reported in [18].…”
Section: Introductionmentioning
confidence: 99%